2015
DOI: 10.1186/s12871-015-0125-6
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of heart rate variability in patients with type 2 diabetes mellitus during spinal anaesthesia: prospective observational study

Abstract: BackgroundLittle is known about the changes in autonomic function during spinal anaesthesia in type 2 diabetic patients. The purpose of the study was to assess the influence of spinal anaesthesia on the heart rate variability in type 2 diabetic patients according to the glycated hemoglobin (HbA1c) level.MethodsSixty-six patients who were scheduled for elective orthostatic lower limb surgery were assigned to three groups (n = 22, each) according to HbA1c; controlled diabetes mellitus (HbA1c < 7 %), uncontrolled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 41 publications
(37 reference statements)
1
5
0
Order By: Relevance
“…who studied the effect of SA on HRV parameters and found that patients with controlled diabetes had significantly decreased low frequency as compared to high frequency. [7]…”
Section: Discussionmentioning
confidence: 99%
“…who studied the effect of SA on HRV parameters and found that patients with controlled diabetes had significantly decreased low frequency as compared to high frequency. [7]…”
Section: Discussionmentioning
confidence: 99%
“…LF showed a slight increase in T2 and a significant increase in T3 in group B. In group C, the LF showed a significant and progressive increase in T2 and T3 times, suggesting an activation of the sympathetic component (Table 3) [13][14][15][16][17].…”
Section: Resultsmentioning
confidence: 92%
“…In the analysis of heart rate variability in the chaos domain, the association of 2 or 3 methods reveals a more complex and more representative information of natural events (approximate entropy, Poincaré plot, DFA, correlation dimension, etc.). The joint analysis through 2 or more indexes allows to estimate the complex, regular or random behavior of the time series, bringing to light information and variables not evident by traditional methods [13]. Despite this, the importance and clinical applicability of these new methods has not yet been defined.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The evaluation of Heart Rate Variability through ECG or heart rate meter is a validated technique used worldwide to evaluate the overall functioning of the autonomic nervous system or its sympathetic and parasympathetic components. Some studies demonstrate the changes in HRV during the installation of subarachnoid anesthesia 7 ; however, no studies were found describing changes in HRV during recovery from anesthesia, or the duration of sympathetic blockade. Figure 1 shows the evolution of the spectrogram during the perioperative period of a patient submitted to an orthopedic surgical procedure under spinal anesthesia.…”
Section: What Do These Findings Mean?mentioning
confidence: 99%